2018
DOI: 10.3390/joitmc4030036
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Development of the WISH (Well-Aging Indexing for Senior Health) Platform for Happiness

Abstract: Humans now have a life expectancy of nearly 90 years and, as a result, society is rapidly aging. These longer life spans have, however, increased the average length of hospitalization for elderly adults suffering from chronic diseases such as cancer, diabetes, and encephalopathy. In a recent survey of 10 well-being indices for elderly adults, the top demands for well-being are physical, spiritual, and psychological. Thus, we developed the WISH (Well-aging Indexing for Senior Health) Platform to enhance the nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In order to maintain the health of elderly people, whose proportion is increasing in an aging society, it is first necessary to support appropriate medical services and nutritional management. In that respect, a standardized platform on nutrition and lifestyle of the elderly developed by Park et al [18] is meaningful. Professional management programs for the elderly and training of professional personnel are also needed [19].…”
Section: The Need For the Development Of Elderly-friendly Food Packagingmentioning
confidence: 99%
“…In order to maintain the health of elderly people, whose proportion is increasing in an aging society, it is first necessary to support appropriate medical services and nutritional management. In that respect, a standardized platform on nutrition and lifestyle of the elderly developed by Park et al [18] is meaningful. Professional management programs for the elderly and training of professional personnel are also needed [19].…”
Section: The Need For the Development Of Elderly-friendly Food Packagingmentioning
confidence: 99%
“…Happiness effects positive emotions that determine quality of life [6]. In this regard, many studies have been conducted on factors related to the happiness of the elderly.While GDP remains widely used as an indicator of a nation's economic activity, it has been consistently found that happiness does not necessarily increase with income, and many international organizations and experts agree that it is necessary to have a happiness index that incorporates not only economic value (e.g., GDP) but also life satisfaction, future expectations, unemployment rate, self-esteem, hope, and love [7,8]. In other words, in order to raise the happiness index of the elderly, a program that can cover not only economic aspects but also psychological aspects is needed.…”
mentioning
confidence: 99%